DEVELOPMENT, CHARACTERIZATION AND PHARMACOKINETIC EVALUATION OF OPTIMIZED VILDAGLIPTIN SUSTAINED RELEASE MATRIX TABLET USING BOX-BEHNKEN DESIGN - GUPTA, SANJAY KUMAR; PATRA, SRADHANJALI (International Journal of Applied Pharmaceutics, 2024)
Objective: The principal objective of this research was to develop and optimize cost-effective sustained-release Vildagliptin (VLN) tablets using the wet granulation method. Methods: The tablets were prepared by the non-aqueous wet granulation method. A Box-Behnken design was used to study the effect of the independent variables, i.e., HPMC K100 M, Eudragit RSPO and PVP K30, on the dependent variables swelling index, in vitro drug release at 8 and 12 h. The drug's physiochemical properties were investigated using ultraviolet (UV), Fourier transform infrared (FTIR) and differential scanning calorimetry (DSC). The hardness, thickness, weight variation, content uniformity, swelling index, and in vitro drug release study of the formulated tablets were all evaluated. The optimized formulation Opt-VLD-SR was evaluated for pharmacokinetic parameters like AUC, Cmax, tmax and MRT. Results: The FTIR and DSC studies confirmed that no interaction occurred between the drug, polymers and excipients. The crystalline nature of VLN remained unchanged in the optimised formulation tablet, according to DSC studies. With the optimal concentration of both polymers, formulation Opt-VLN delayed drug release for up to 12 h. The formulated Optimized Sustained-release tablets (Opt-VLD-SR) showed significantly lower Cmax±3.01ng/ml) than conventional IR tablets (256.17±8.02ng/ml). In the pharmacokinetic study, the MRT for Optimized-VLD-SR is (7.40h) showed a better result than the Vildagliptin IR marketed product (3.70 h.), which leads to higher bioavailability of Vildagliptin. Conclusion: Sustained release tablets of VLN with a combination of diffusion and erosion-controlled drug release mechanisms have been successfully developed.